PENGARUH PENERAPAN MEDIA PUZZLE PECAHAN TERHADAP HASIL BELAJAR SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN KELAS IV SD NEGERI 9 INPRES SASANDE - Silkiah Ananda; Rahmawati Patta; Hardianto Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of fraction puzzle media in teaching addition and subtraction of fractions in the fourth grade of SD Negeri 9 Inpres Sasande Majene, to describe students’ learning outcomes, and to determine the effect of using fraction puzzle media on students’ learning outcomes. This research is categorized as an experimental study with a quantitative approach and applies a pre-experimental design (nondesign) type of one sample pretest-posttest. The population consisted of all fourth-grade students of SD Negeri 9 Inpres Sasande Majene, with a total sample of 19 students selected using the saturated sampling technique. Data were collected through observation sheets to assess the implementation of fraction puzzle media, learning outcome tests, and documentation. The data were analyzed using descriptive and inferential statistics. The descriptive analysis showed that the implementation of the learning process using fraction puzzle media was in the “very good” category. Students’ learning outcomes before the treatment were in the “good” category and improved to the “very good” category after the treatment. Inferential analysis using a paired t-test indicated a significant difference in learning outcomes after the treatment. Therefore, it can be concluded that the use of fraction puzzle media has a significant effect on students’ learning outcomes in addition and subtraction of fractions for fourth-grade students of SD Negeri 9 Inpres Sasande Majene.